PERAN PENGADILAN AGAMA DALAM KEADILAN EKONOMI SYARIAH UNTUK ANAK KORBAN PERCERAIAN - Fatimah, Siti; Patrajaya, Rafik (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
Child protection is a crucial aspect in realizing social justice, especially in families experiencing divorce. In the context of Islamic economics, there are principles such as justice (al-'adl), public good (maslahah), and preservation of the soul (hifz al-nafs) that are relevant in protecting children's rights. This study aims to analyze the role of religious courts in realizing Islamic economic justice for children who are victims of divorce, who are often the main caregivers of the family. This study uses a qualitative method with a case study approach, where data was collected through document analysis from religious courts and data from the Indonesian Child Protection Commission (KPAI) until September 2023. Divorce data in Central Kalimantan in 2023 shows that continuous disputes and quarrels are the main causes of divorce, which have the potential to impact violations of children's rights, such as access to meet parents and fulfillment of sustenance. Domestic violence (KDRT) that causes divorce is also related to cases of physical and psychological violence against children, as reported by the KPAI. These findings indicate that divorce and domestic violence contribute to the increasing cases of children being victims of violence and rights violations. The results of the study show that religious courts have a significant role in ensuring that children's rights are met, especially in aspects of care, education, and health. Decisions made by religious institutions are often based on Islamic economic principles that emphasize holistic child welfare. In addition, religious courts also function as guardians of children's civil rights, ensuring that they are not only protected from physical and psychological violence, but also have access to proper education and health services. This study emphasizes the importance of the role of religious courts in upholding justice for children who are victims of divorce, in accordance with the principles of Islamic economics.